ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PERILAKU DISFUNGSIONAL AUDIT ( Studi Empiris Pada KAP di Jawa Tengah) - Pipiet Dwi Puspitarini, 13.05.52,0084; Badjuri, Achmad (Students' Journal of Accounting and Banking, 2018)
This study was conducted to determine the analysis of the factors that affect the price of shares in manufacturing companies in Indonesia Stock Exchange . This research was conducted at the companies listed on the stock exchanges of Indonesia in 2010-2012. Data derived from the audited financial statements in IDX and ICMD 2010 to 2012. The samples in this study were taken by using purposive sampling method . From the results of research conducted by multiple linear regression analysis method is known that CR significantly positive effect on stock prices , then H1 : Liquidity significant positive effect on stock prices received . ROE no significant effect on stock prices , then H2 : Profitability significant positive effect on stock prices on the decline . Sales growth is not a significant effect on stock prices , then H3 : Sales pertumbuan significant positive effect on stock prices on the decline . EPS significant positive effect on stock prices , then H4 : EPS significant positive effect on stock prices received .Keywords: stock price, Liquidity, Profitability, Sales Growth, EPS.